Classification of Music Instruments: An overview - Poudel, Parsuram Prasad (International Research Journal of MMC, 2021)
Varieties of music instruments are available today to produce the audible sounds which are used to make a piece of music. The music instruments have been classified into various groups depending upon the size, materials, usages, structure, and others. But, today many new practices, experiments, devices, and new instruments have been emerged with the flow of time in musical field. For all the concerned with music, a neo-classification of instruments is ever raised a question. So, from the educational point of view, some of the new music instruments, which are played today, further should be re-classified for convenience. The present article is based on an overview upon the study about the music instruments by following the secondary data and analytical method. After interpretation and analysis, some music instruments, which are still unclassified are categorized under neo-classification.